Analisis Kepuasan Pengguna E-Commerce Shopee Menggunakan Model End-User Computing Satisfaction (EUCS) - Asasunnaja, Rinny; Fatwanto, Agung; Putra, Dwipa Junika (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2025)
Technology is currently developing very rapidly, one of the advantages with the presence of technology is that business can be done online without being limited by distance and time and the activity of business transactions is known as e-commerce. One of the e-commerce that is famous and in demand by many buyers in Indonesia is the shopee e-commerce application, this research aims to determine the satisfaction of e-commerce customers in using the shopee application using the EUCS model. This research used a quantitative method with a purposive sampling technique which resulted in a sample of 277 respondents. The results of the research conducted on the R2 test, it is known that the R Square value is 0.686, which means that variable of content, accuracy, format, ease of use and timeliness simultaneously affects the satisfaction variable by 68.6%. Furthermore, from the results of the T test, it can be seen that there is an effect of the variables of content, format, ease of use and timeliness on the satisfaction variable, but the accuracy variable has no effect on the satisfaction variable. And the researcher carried out an F test in this study, and the results of the F test showed that the significant value for the influence of the variables content, accuracy, format, ease of use and timeliness simultaneously had an influence on the user satisfaction variable.